Does one heavy load back squat set lead to postactivation performance enhancement of three-point explosion and sprint in third division American football players? - Robert Bielitzki; Daniel Hamacher; Astrid Zech (BMC, 2021)
Abstract Background American football players need the ability to provide maximal muscular power in a modicum of time. Postactivation performance enhancement (PAPE), which is characterized by an acute improvement of a performance measure following conditioning contractions, could be of value for American football players. The aim of the present study was to determine the effect of a heavy load back squat PAPE protocol on three-point explosion (TPE; an essential blocking technique and drill) and 40-yard dash (40YD) performance compared to a traditional warm-up in American football players. Methods In a crossover study design, eighteen male competitive regional league American football players (mean ± SD: body mass 93.9 ± 15.5 kg, height 181.4 ± 6.8 cm, age 24.8 ± 3.9 years) performed a TPE on a double blocking sled (weight: 150 kg) and a 40YD (36.6 m with a 5 and 10 m split) 8 min after two different warm-up conditions. One condition was a traditional, football specific warm-up (TWU) consisting of game related movements (e.g. backward lunges, lateral power steps), whereas the other condition (PAPE) consisted of three explosive back squats with a load of 91 % one-repetition maximum. Results There was no significant difference in TPE between TWU and PAPE. For the 40YD, we found significantly shorter sprint times in the PAPE condition with medium effect sizes for the 5 m (p = 0.007; r = 0.45) and 10 m (p = 0.020; r = 0.39) but not for the whole 36.6 m distance (p = 0.084; r = 0.29) compared to the TWU condition. Conclusions The used heavy load back squat PAPE protocol improved sprint performance over short distances (≤ 10 m) but not complex movements like the three-point explosion.